The Power Balance Issues in the Semi-Presidential Republic - Tsanava, Lana (Journal of Law, 2017)
Creation of a semi-presidential system is related to the second wave of rationalization of Parliamentarism. In this event, enhancement of the executive authority has gained far wider scale than implemented by the authors of the Bonn Constitution. Weakening of the legislative body at the account of strengthening of the executive authority is clearly evident in the system, which entails significant discourse in the context of checks and balances of power. The hereby article aims to analyze the hereof problem, to study and estimate the theoretical and practical aspects of the semi-Presidential Republic.